An examination of driving speed: the role of perceivable road characteristics in towns - Martin Scháno; Josef Nový; Jiří Zeisek (Acta Polytechnica CTU Proceedings)
Understanding the subjective perspectives of drivers is paramount in evaluating the factors affecting driving speed in built-up areas. Building on our previous work, where a wide set of infrastructure attributes was analysed, this paper delves deeper into the realm of driver perception. It seeks to answer how drivers’ observations and awareness of their surroundings influence their speed choices. We reconduct our previous analysis, emphasizing the driver’s subjective viewpoint, contemplating the visible and perceivable elements of the road infrastructure rather than their objective presence. This research aims to garner insights into how these subjective elements impact speed choices. This research has uncovered a number of interesting factors that have not been previously used in the calculation of road vehicle speeds. This more nuanced understanding is expected to lead to enhanced safety and efficiency in road traffic management, ensuring the road design aligns seamlessly with driver perception and behaviour.